Public Services of Muhammadiyah: The Theology of Al-Maun and the LAZISMU Zero Amil Rights - Nur Aida Ikrima; Mukhammad Ali Turdialiev Polatjon Ogli; Odilbek Khazratkulov; Clarizze Yvoine Mirielle; Arief Budiono; Kelik Wardiono (Universitas Muhammadiyah Malang, 2024)
One of the core foundations of the movement of Muhammadiyah (Indonesia's second-largest Muslim organization) is the theological strength of the al-Ma’un Qur’anic chapter which was taught by Ahmad Dahlan, Muhammadiyah’s founder. Dahlan interpreted al-Ma’un into three main activities, namely education, health, and charity of the poor. He also transformed religious understanding from mere sacred doctrines that are socially